Os fatores determinantes do preço da mensalidade do curso de administração a distância - Soares, Débora Regina Diniz (2015)
In recent decades the market of private higher education experiences a constant expansion and go through several transformations that led to a deep growth of supply and demand, promoting, therefore, distance education. The Cournot Model provided theoretical grounding for understanding market. It was used a log-log model with data in cross section with application of robust standard errors of White. Comparing the results presented to the theory, the model met the econometric requirements. In the overall analysis, the results showed that the variables used in the model are determinant to explaining the variation in the tuition price of business course in distance education. Individually, the independent variable that presents the most impactful refers to income, in this study, represented by the gross domestic product of cities in 2010.